2020
DOI: 10.1002/jmv.26157
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary and atypical clinical presentations of COVID‐19

Abstract: The novel coronavirus (SARS-CoV2) has led to an outbreak of multiple cases of pneumonia in Wuhan city in December 2019. The disease caused by this virus was named coronavirus disease 2019 or "COVID-19", which was declared by the World Health Organization as a global pandemic in March 2020. It typically presents with respiratory symptoms and febrile illness. However, there are few reported extrapulmonary and atypical presentations, such as hemoptysis, cardiac, neurological, gastrointestinal, ocular, and cutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 53 publications
(137 reference statements)
0
107
0
10
Order By: Relevance
“…While COVID-19 mainly causes lung injury and severe hypoxic respiratory failure, many studies have reported extrapulmonary manifestations as well. Some of the recent data have suggested neurological, cardiac, gastrointestinal, ocular, renal, and cutaneous manifestations of COVID-19 [ 1 , 2 , 4 ]. However, there is no indication in the current data showing a link between SARS-CoV-2 and hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…While COVID-19 mainly causes lung injury and severe hypoxic respiratory failure, many studies have reported extrapulmonary manifestations as well. Some of the recent data have suggested neurological, cardiac, gastrointestinal, ocular, renal, and cutaneous manifestations of COVID-19 [ 1 , 2 , 4 ]. However, there is no indication in the current data showing a link between SARS-CoV-2 and hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID-19 is mainly a respiratory disease characterised by pulmonary manifestations, reports on extrapulmonary manifestations are not uncommon in the published literature. Some of these include gastrointestinal, cardiac, neurological and cutaneous manifestations, features of renal and liver dysfunction, as well as taste and smell disorders [33,34]. Patients with gastrointestinal involvement may present with symptoms such as diarrhoea, vomiting, abdominal pain and loss of appetite [35] whereas neurological manifestations such as encephalitis, encephalopathy, stroke and Guillain Barre Syndrome have been reported [9].…”
Section: Clinical Characteristics In Generalmentioning
confidence: 99%
“…Fever, cough, shortness of breath, anosmia, ageusia, or dysgeusia are the most common symptoms of COVID-19. However, a wide variety of atypical presentations have also been described [ 1 ]. Some uncommon presentations are related to the hypercoagulable state, while others are a result of the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%